Biomolecular actuators for genetically selective acoustic manipulation of cells - Wu, Di; Baresch, Diego; Cook, Colin; Ma, Zhichao; Duan, Mengtong; Malounda, Dina; Maresca, David; Abundo, Maria P.; Lee, Justin; Shivaei, Shirin; Mittelstein, David R.; Qiu, Tian; et al. (Science advances, 2023)
The ability to physically manipulate specific cells is critical for the fields of biomedicine, synthetic biology, and living materials. Ultrasound has the ability to manipulate cells with high spatiotemporal precision via acoustic radiation force (ARF). However, because most cells have similar acoustic properties, this capability is disconnected from cellular genetic programs. Here, we show that gas vesicles (GVs) - a unique class of gas-filled protein nanostructures - can serve as genetically encodable actuators for selective acoustic manipulation. Because of their lower density and higher compressibility relative to water, GVs experience strong ARF with opposite polarity to most other materials. When expressed inside cells, GVs invert the cells’ acoustic contrast and amplify the magnitude of their ARF, allowing the cells to be selectively manipulated with sound waves based on their genotype. GVs provide a direct link between gene expression and acoustomechanical actuation, opening a paradigm for selective cellular control in a broad range of contexts.
Gesehen am 12.12.2023